2010
DOI: 10.1164/rccm.200910-1643oc
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Oscillatory Power Is a Constant Fraction of Total Power Irrespective of Pulmonary Artery Pressure

Abstract: In this study, oscillatory power fraction is constant at 23% in non-PH and IPAH, implying that a considerable amount of power is not used for forward flow, making the RV less efficient with respect to its arterial load. Our findings emphasize the need to develop new therapy strategies to optimize RV power output in PAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(97 citation statements)
references
References 25 publications
3
93
1
Order By: Relevance
“…Oscillations play a more important role in the pulmonary vascular bed and, therefore, the RV oscillatory power fraction is much larger (23-33%) [36,55] than in its systemic counterpart. However, in contrast to systemic hypertension oscillatory power fraction remains constant in pulmonary hypertension [53].…”
Section: Comparison Of Pulmonary and Systemic Circulationmentioning
confidence: 85%
See 1 more Smart Citation
“…Oscillations play a more important role in the pulmonary vascular bed and, therefore, the RV oscillatory power fraction is much larger (23-33%) [36,55] than in its systemic counterpart. However, in contrast to systemic hypertension oscillatory power fraction remains constant in pulmonary hypertension [53].…”
Section: Comparison Of Pulmonary and Systemic Circulationmentioning
confidence: 85%
“…It has been found that oscillatory power is ,23% of total power (and mean power plus oscillatory power being total power is 23/(100-23)5 23/77 or ,30% of mean power), and that this fraction is remains the same in healthy subjects Reproduced from [27] with permission from the publisher. and in subjects with PAH [53]. This constant fraction is the result of the proportionality of pressures, (mean over systolic pressure) and, therefore, also follows on from the constancy of RC.…”
Section: Consequences Of the Constant Product Of Resistance And Complmentioning
confidence: 87%
“…To assess RV function, we calculated RV mean power, expressed in joules per second, as HR Â mPAP Â stroke volume (SV) Â 2.22 Â 10 −6 , at rest and at maximum exercise. 8 The relationship between ΔmPAP and ΔQt was assessed both graphically and by calculating the slopes of these relationships from the 3 study points (rest and submaximal and maximal exercise) for individual patients. We also calculated total PVR indexed to BSA (TPVRi), calculated as mPAP/CI.…”
Section: Methodsmentioning
confidence: 99%
“…intraventricular pressure minus intrapericardial pressure. During ejection, intraventricular pressure depends on pulmonary artery pressure, which itself depends on CO, pulmonary vascular resistance and compliance [9].…”
Section: Preload and Afterloadmentioning
confidence: 99%